Determination of a-ferrite in welded chromium nickel stainless steel parts - Bela, Sabo; Šiđanin, Leposava; Pantelić, Mihailo; Dakić, Jovica; Brestovački, Lazar (Journal of Production Engineering, 1994)
The present paper is concerned with quantification of a-ferrite in weld joints. For that purpose, the chromium nickel stainless parts were used which were previously treated by the TIG process. To produce a different amount of ferrite, the different filler materials were used, either standard materials or cut strips from steel plates. In the case of tutted strips, the best results were obtained in conditions where the base material 0.4580 was welded with cut strips of 0.4580 as filler material. For other combinations, the hot cracking was identified.